2020
DOI: 10.1039/d0cp00907e
|View full text |Cite
|
Sign up to set email alerts
|

The infrared spectra of protic ionic liquids: performances of different computational models to predict hydrogen bonds and conformer evolution

Abstract: DFT calculations with the ωB97-D functional reproduce hydrogen bonding features of the far-infrared spectra of diethylmethylammonium methanesulfonate and diethylmethylammonium trifluoromethanesulfonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 38 publications
5
35
1
Order By: Relevance
“…These results are in good agreement with previous investigations on the same ions [32]. Recently, it has been shown that a good agreement between the calculated and the experimental infrared spectrum of the protic ionic liquid DEMA-TfO can be obtained by exploiting DFT calculations on the ionic couple with the ωB97X-D functional, including empirical dispersion corrections and the presence of a polar solvent (dimethylformamide, εr = 37.22) [49]. Here, we want to investigate whether this better agreement is visible also in the case of the presently investigated non-protic IL.…”
Section: Computational Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…These results are in good agreement with previous investigations on the same ions [32]. Recently, it has been shown that a good agreement between the calculated and the experimental infrared spectrum of the protic ionic liquid DEMA-TfO can be obtained by exploiting DFT calculations on the ionic couple with the ωB97X-D functional, including empirical dispersion corrections and the presence of a polar solvent (dimethylformamide, εr = 37.22) [49]. Here, we want to investigate whether this better agreement is visible also in the case of the presently investigated non-protic IL.…”
Section: Computational Resultssupporting
confidence: 90%
“…The calculated angle formed by the C2, H2 and O1 atoms is 136.6 • , a value slightly lower than the experimental value of 149 • , which, however, was reported for the solid phase of EMI-TfO [51]. It must be noted that the most evident change induced by considering the presence of a solvent in the DFT calculations is enlargement of the distance between anion and cation in similar ionic couples containing TfO [49], and, indeed, this approach allows to correctly evaluate the H2-O1 distance.…”
Section: Computational Resultscontrasting
confidence: 56%
See 3 more Smart Citations